Teachers’ Challenges in Implementing Pedagogical Deep Learning Approaches in English Classrooms at Central Java Junior Islamic School - Dimas Septiano Saputra; Anam Sutopo (Lingua Susastra, 2026)
The implementation of pedagogical deep learning under Indonesia's Merdeka Curriculum presents unique challenges for English as a Foreign Language (EFL) teachers within Islamic secondary school (madrasah) contexts. This qualitative case study investigates the specific classroom challenges and adaptive teaching strategies of EFL educators implementing this approach at MTSN 2 Surakarta. Research data were gathered through semi-structured interviews, extensive classroom observations, and instructional document analysis, and subsequently analyzed using Braun and Clarke's thematic analysis framework. The findings reveal seven primary challenges: limited student vocabulary, low learning motivation, diverse student abilities, restricted instructional time, inadequate facilities, curriculum changes, and insufficient teacher readiness. To overcome these hurdles, teachers deployed adaptive strategies including project-based learning, peer teaching, technology integration, and contextualized higher-order thinking skills (HOTS) activities. This study underscores the complex interaction between madrasah institutional culture and curriculum reform, concluding that continuous professional development, robust institutional support, and contextualized pedagogical innovations are vital for sustainable classroom implementation.